Assembly of shell/core CDs@CaF2 nanocomposites to endow polymers with multifunctional properties. (12th February 2019) - Hu, Guangqi; Sun, Yuqiong; Wu, Shuangshuang; Li, Wei; Hu, Chaofan; Zhuang, Jianle; Zhang, Xuejie; Lei, Bingfu; Liu, Yingliang
Abstract: The shell/core structure of CDs@CaF2 nanocomposites (CCNCs) were prepared by assembling fluorescent carbon dots (CDs) inside the inorganic CaF2 substrates using co-precipitation interaction. CDs endow CaF2 with properties of good UV-absorbing behavior and efficient blue light emission instead of rare-earth such as Eu that is expensive and susceptible to polluting the environment during the mining process. Due to the nanometer size and surface effect of nano CaF2, and the approximate refractive index between CaF2 and polyethylene (PE), CCNC/PE film exhibits better elongation at the break than pure PE film while maintaining high transparency and visible light transmittance. Simultaneously, the CCNC/PE film was experimentally demonstrated to have outstanding performance of anti-UV and blue light conversion, which shows that CCNCs can be a novel and promising multifunctional additive applied in polymers especially for greenhouse film.